Software Export Marketing : Problems and Prospects (Suggesting Suitable Strategy) - Nigam, Ashutosh (Journal of Commerce and Trade, 2008)
Significant market competition exists in the world software market for Indian software exporting firms. To make their presence felt in international market the Indian Software exporting firms have to develop suitable software export marketing strategy by focusing its core competency areas and developing the practices of international standards. The marketing strategy for software products is especially relevant where normal selling fails to deliver the required results and to make made in India label a symbol of software quality, competitive price, reliability and service to the customers.